The Effect Of Raw Material Inventory And Machine Maintenance On Production Results (Case study on An-Nadiyah Embroidery Convection Tasikmalaya City) - Ilham Akbar Nugraha; Suci Putri Lestari; Barin Barlian (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the Effect of Raw Material Inventory and Machine Maintenance on Production Results Case study on An-Nadiyah Embroidery Convection Tasikmalaya City). The method used in this study is a casual associative method (cause and effect) with a quantitative approach, as for the sample, namely data on the cost of Raw Material Inventory, Machine Maintenance costs, and production data for the last 4 years or the last 48 months, namely in the period January 2019-December 2022 on An-Nadiyah Embroidery Convection. The analysis tool used in this study was multiple linear regression using SPSS Version 25. The results showed that simultaneously the discipline of Raw Material Inventory and Machine Maintenance had a significant effect on production results. Partially, the Standard Bahn Inventory has a significant effect on production output. Partial Machine Maintenance has a significant effect on Production Results.